Biochemical Characterization of Antimicrobial Sensitivities of Mycobacteria Causing Pulmonary Tuberculosis in HIV and Non-HIV Positive Patients - Kyei, B.G. (University of Ghana, 2003)
The purpose of this study was to find out the species of mycobacteria causing pulmonary tuberculosis in HIV and non-HIV seropositive patients in Accra, Ghana, and to determine the drug susceptibility patterns in the two groups of patients. From November 2002 to March 2003, new patients attending the Chest Clinic of the Korle-Bu Teaching Hospital and diagnosed with tuberculosis by sputum smear microscopy were enrolled. Patient sputum was cultured and drug susceptibility testing done for Isoniazid (I), Rifampicin (R), Ethambutol (E) and Streptomycin (S). HIV/AIDS testing was also carried out for consenting patients. In all 96 patients were enrolled. Of the 92 patients who were tested for HIV, 22 (23.9%) were seropositive for the virus. Sixty-six isolates were obtained, out of which 61 (92.4%) were Mycobacterium tuberculosis complex strains while the remaining were environmental mycobacteria. For the Mycobacterium tuberculosis complex strains, overall drug resistance (resistance to one or more drugs) was 50.8% (95% Ci 38.3-63.3), with an initial multi-drug resistance rate of 4.9%. Percentage resistances to the various drugs were Isoniazid (4.9%), Ethambutol (24.6%), Rifampicin (26.2%) and Streptomycin (34.4%). There was no significant association between HIV seropositivity and sputum smear results, drug susceptibility or species of mycobacteria isolated. It was however found that environmental mycobacteria were more likely to be resistant to streptomycin (p=0.04) and rifampicin (p=0.01). The study found high initial resistance to the first line drugs for treating tuberculosis in Accra and its surrounding towns.